Modeling of crack growth process in spatial bodies under cyclic loading condition - Bazhenov, V.; Pyskunov, S.; Shkryl, O. (KNUCA, 2014)
The algorithm for finite element modeling of fatigue cracks growth in the spatial bodies under cyclic loading using semianalytic finite element method (SFEM) is presented. The crack growth process is described by Paris' equation, stress intensity factor (SIF) is determined by the direct method. Testing of the algorithm is executed on the problem of the development of an elliptical crack in a prismatic body under the action of cyclic loading.
Моделирование развития трещин в пространственных телах при циклической нагрузке
Keywords: cyclic loading condition; crack; fracture mechanic; lifetime; spatial problem; semianalytic finite element method (SFEM); циклическая нагрузка; трещина; механика разрушения; ресурс; пространственная задача; ароуаналитический метод конечных элементов (ПМКЭ)